Ethics of justice vs the ethics of care in moral decision making - A. Botes (AOSIS, 1998)
The question to be addressed in this paper is : How can the ethics of justice and the ethics of care be used complementary to each other in ethical decision making within the health care team? Various arguments are presented that justify the reasons that the ethics of justice and the ethics of care should be used complementary to each other for effective ethical decision making within the health care team. The objective is to explore and describe the compatibility of the ethics of justice and the ethics of care from two perspectives: firstly an analysis of the characteristics of the two ethical theories, and secondly the scientific-philosophical viewpoints of these theories. The two theories are incompatible when viewed from these perspectives. For a probable solution to this incompatibility arguments are presented from the perspectives of reflection and virtue-based ethics.